Effects of dietary Astragalus membranaceus (Fisch.) Bge. root extract on growth performance, plasma biochemical parameters, fish composition, liver and intestinal morphology, and genes expression in head kidney of hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) - Zhenzhu Sun (Elsevier, 2022)
In recent years, plant extracts have been paid more and more attention as immune enhancers for aquatic animals instead of antibiotics. In the present study, the effects of Astragalus membranaceus extract on growth performance, body composition, plasma biochemistry analysis, intestinal and liver histology and gene expression were investigated in hybrid groupers (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀). Five groups of experimental diets were prepared by adding different levels (0%, 0.1%, 0.2%, 0.4%, and 0.8%) of Astragalus extract in the basal diet. Samples were collected at the end of the 8-week feeding experiment. The results showed that Astragalus extract (AE) had no significant effect on the weight gain rate and feed efficiency ratio of hybrid grouper (P > 0.05). There were no significant difference of the contents of crude protein, crude lipids, moisture and ash in the whole body and muscle of hybrid groupers (P > 0.05). The villous structure of the foregut and midgut, the hepatocyte size and the integrity of cell membrane in each experimental group has no significant changes too. The changes of villus length in the hindgut becomes longer as the increases of AE addition. The addition of 0.1% and 0.2% of AE significantly reduced serum cholesterol content (P < 0.05). The relative mRNA expressions of Caspase 9, Keap1 and IL-8 in head kidney of fish showed a significant increase trend with the addition of AE (P < 0.05). The results showed that dietary AE could not significantly improve the growth performance and liver morphology even though could improve hindgut morphology of hybrid grouper.